Armchair tourism: exploring individuals’ innovative travel experience in the with-corona era - Moon, Hyoungeun; Yu, Jongsik; Chua, Bee-Lia; Han, Heesup (Elsevier, 2022)
This study investigates the experiential components of armchair travelling and their effect on the armchair travelers’ responses, which include perceived authenticity, destination image, and behavioral intention, by using a mixed-method approach. A total of 414 survey responses collected through an online research panel were analyzed by conducting a confirmatory factor analysis and structural equation modeling. The analysis reveals that a sense of telepresence and copresence are the major factors, which generate authenticity and a positive destination image. Perceived ease of use influences building a favorable destination image, whereas self-other online interactions significantly create a sense of authenticity with the armchair travel experience. The content analysis for the qualitative data collected using an open-ended question shows that the armchair travelers gain vicarious travel experiences and resolve mental stress through armchair travelling. Based on the results, this study provides meaningful theoretical and practical implications to the armchair tourism literature and industry.